2015
DOI: 10.4049/jimmunol.1402658
|View full text |Cite
|
Sign up to set email alerts
|

K+ Efflux Agonists Induce NLRP3 Inflammasome Activation Independently of Ca2+ Signaling

Abstract: Perturbation of intracellular ion homeostasis is a major cellular stress signal for activation of NLRP3 inflammasome signaling that results in caspase-1 mediated production of IL-1β and pyroptosis. However, the relative contributions of decreased cytosolic [K+] versus increased cytosolic [Ca2+] remain disputed and incompletely defined. We investigated roles for elevated cytosolic [Ca2+] in NLRP3 activation and downstream inflammasome signaling responses in primary murine dendritic cells and macrophages in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
189
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(202 citation statements)
references
References 62 publications
(94 reference statements)
11
189
1
1
Order By: Relevance
“…Because 2-APB non-selectively modulates many ion channels besides CRAC channels as discussed above, and BAPTA suppresses all intracellular Ca 2+ signaling, these data collectively suggest that Ca 2+ signals (potentially mediated by P2X7 receptors or Ca 2+ release from ER stores) but not SOCE are required for NLRP3 inflammasome activation. Given recent reports that K + efflux but not Ca 2+ influx is essential for NLRP3 activation (85, 86) further studies if and how Ca 2+ signaling exactly contributes to NLRP3 inflammasome activation are required.…”
Section: Discussionmentioning
confidence: 99%
“…Because 2-APB non-selectively modulates many ion channels besides CRAC channels as discussed above, and BAPTA suppresses all intracellular Ca 2+ signaling, these data collectively suggest that Ca 2+ signals (potentially mediated by P2X7 receptors or Ca 2+ release from ER stores) but not SOCE are required for NLRP3 inflammasome activation. Given recent reports that K + efflux but not Ca 2+ influx is essential for NLRP3 activation (85, 86) further studies if and how Ca 2+ signaling exactly contributes to NLRP3 inflammasome activation are required.…”
Section: Discussionmentioning
confidence: 99%
“…ATP is released by damaged cells, triggering K+ efflux via stimulation of the ATP-gated P2X7 ion receptor [14,15]. High levels of ATP are detected in serum of chronic ethanolfed mice [10].…”
Section: Mediators Of Inflammasome Activators In Alcoholic Liver Diseasementioning
confidence: 99%
“…We recently reported that the kinetics of nigericin-induced propidium 2ϩ influx tracks with accumulation of active caspase-1 as an early index of the change in plasma membrane permeability that defines pyroptosis (34). Intracellular accumulation of the normally impermeant propidum 2ϩ via increased plasma membrane permeability facilitates its intercalation with DNA resulting in increased 540 3 620 nm fluorescence.…”
Section: Nigericin-induced Assembly Of Nlrp3 Inflammasomes Mediates Rmentioning
confidence: 99%